Gastrointestinal Cancers with Consideration of DPD and UGT1A1 Plasma Levels: Chemotherapy-Related Toxicity - Velko Minchev; Hristo Tsankov; Bozil Robev; Martin Takov; Stefan Federchev; Kalina Kamenova; Lozan Todorov; Liliya Atanasova; Nadya Hristova-Avakumova; Rumen Nikolov; Pavlina Gateva; Vanyo Mitev (Life, 2025)
Unpredictable, dose-limiting toxicity remains a challenge in cancer treatment. We evaluated dihydropyrimidine dehydrogenase (DPD) and UDP-glucuronosyltransferase 1A1 (UGT1A1) plasma levels in the context of chemotherapy-induced toxicity and disease progression. Seventy gastrointestinal cancer patients (30 FOLFOX; 40 FOLFIRI) were enrolled. DPD and UGT1A1 plasma levels were determined using ELISA. Univariable and bivariable analyses and a general linear model (GLM) framework were used. Post-infusional reductions in white blood cell and granulocyte counts were observed. For FOLFOX, the granulocyte counts decreased by 17% (r = 0.54; p = 0.0030), while FOLFIRI caused a 41% reduction (r = 0.43; p = 0.0063). DPD levels were lower in FOLFOX than in FOLFIRI (2.543 vs. 3.579; p = 0.0363; Cohen’s d = 0.52). The multiple linear regression models associated DPD levels with cancer progression (b* = 0.258, p = 0.034). The bivariate analysis and multiple linear regression indicated some trends of association between UGT1A1 levels and reduction in white blood cell (b* = 0.359, p = 0.042) and granulocyte counts (b* = 0.383, p = 0.030) among FOLFIRI-treated patients. These preliminary observations suggest that DPD and UGT1A1 might contribute to evaluating response assessment.